Symbolic Violence in the Short Story Anthology SAIA The work of Djenar Maesa Ayu - Laila Nur Azizah; Teguh Supriyanto; Yusro Edy Nugroho (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The aim of the research is to describe the symbolic violence contained in the short story anthology SAIA by Djenar Maesa Ayu. Data collection was carried out using heuristic techniques and content analysis techniques by listening and noting the required parts in the text. The data in this research are words, sentences, sentence fragments, paragraph fragments which are classified using data cards to be analyzed using hermeneutic techniques. The results of data analysis show that there is a structuration of power which is manifested in the form of capital, class, habitus and arena.